Programas de formação continuada de professores da rede pública municipal de ensino de Limeira (1996 – 2012) - Silva, Juliana Bueno da (2017)
This work presents the programs of continuous teacher training in the municipal public-school system of Limeira, from 1996 to 2012, when different continuing education programs with different theoretical and methodological orientations were developed. In our research, we used qualitative research processes, conducting bibliographical and documentary researches, which made it possible to conceptualize the continuing education of teachers, analyze official documents of the municipal public-school system of Limeira and the educational programs of continuing education, highlighting their objectives, conceptions, types of training, methodologies and results. This research also presents the Municipal Center for Pedagogical Studies, CEMEP (1997-2012), which showed as a ―study center‖ to discuss, capacitate, acquire new knowledge and improve educators in their didactic-pedagogical training. The analyzed programs are: Total Quality Program in Education, PQTE (1996), Pedagogical Workshops (1996), Parameters in Action (1999), the ―Pro-Trainer‖ Program (2000), Estudar Pra Valer (2004), Letra e Vida (2006), Reading and Writing (2008), and the National Pact for Literacy in the Right Age, PNAIC (2012). I believe that the continuing training developed during the period of this study played an important role in the formation and consolidation of the teaching and technical staff of the network.